Физическая культура как фактор валеологического и экологического воспитания студентов - Abdukarimov, Nurmaxan; Zholdasbekova, Bibisara (Физическое воспитание, спорт и здоровье, 2021)
In this article, the main categories and concepts that allow to present the ecological education of students in the perspective ofphysical culture of'the individual are defined. The functions examined by its allow the student to master various technologies of ecoTogicaT education and'physical education of the person, which ensure the formation of ecological consciousness and ecological culture. Among these functions are: information, development, orientation, mobilization, constructive, communicative, organizational and research. All these functions are closely related to each other in the integral structure of a specialist's personality and can form the basis of his professional activity in relation to environmental education and human education. The priority of human life and health as a fundamental principle of the state policy of the Republic of Kazakhstan in the field of education is fixed in the Law of the Republic of Kazakhstan "On Education ”. These circumstances allow us to state that the problems of the development of the valeological potential of a person's physical culture and the ecological of a person's consciousness acquire the status of global problems of the present. Taking into account certain aspects of human ecology and valeology, one can determine the leading goal of environmental education. It consists, in the formation of an environmentally oriented person. An ecologically active personality is a person possessing an eccentric type of ecological consciousness. In this regard, the overall task of environmental education can determine the formation of the ecological consciousness of the individual. This target is specified in three main objectives of environmental education: A) formation of adequate ecological representations; В)formation of altitude towards nature; С)orienting the system of skills and the skill (technology) of interaction with nature. Proceeding from the element analysis of the above phenomenon, it can be stated that the goal of physical and ygical education at the present stage should consist in the development of readiness to use the achievements of ical culture to preserve the health and high working capacity of a person for a long period of life.